2014
DOI: 10.3758/s13423-014-0618-1
|View full text |Cite
|
Sign up to set email alerts
|

Active maintenance of semantic representations

Abstract: In research on verbal working memory, articulatory rehearsal, a maintenance mechanism for phonological representations, has undergone intensive and excellent study. Possible mechanisms for semantic representation have received less attention. However, several studies have reported a double dissociation in types of memory deficits (semantic memory difficulties vs. phonological memory difficulties). This suggests the separability of two maintenance mechanisms. The present study focused on this separability in in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
21
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 35 publications
6
21
1
Order By: Relevance
“…Of note, the interaction between memory task and dual task indicates selective disruption of synonym recognition by tapping. The results replicated the findings of Nishiyama [ 25 ], using a more appropriate phonological memory task and a secondary task with a more standard pace.…”
Section: Experiments 1asupporting
confidence: 85%
See 2 more Smart Citations
“…Of note, the interaction between memory task and dual task indicates selective disruption of synonym recognition by tapping. The results replicated the findings of Nishiyama [ 25 ], using a more appropriate phonological memory task and a secondary task with a more standard pace.…”
Section: Experiments 1asupporting
confidence: 85%
“…However, Nishiyama [ 25 ] demonstrated a double dissociation in which tapping disrupted the performance of a modified synonym recognition task [ 26 , 27 ] and AS disrupted the performance of the homophone recognition task, selectively. The synonym recognition task required participants to choose synonyms for studied words as recognition targets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies with normal participants have also demonstrated similar double dissociations (Nishiyama, 2013(Nishiyama, , 2014. For example, using a dual-task interference paradigm, Nishiyama (2014) showed that disrupting maintenance of words using articulatory suppression or tapping differently affected performance on a homophone (phonological) or synonym (semantic) short-term recognition task.…”
Section: Semantic Representations In Working Memorymentioning
confidence: 93%
“…However, the recent-probes task provides a measure of interference due to temporal recency in recognition memory, which is different to the buildup of PI due to semantic context in free recall. There is increasing evidence that the maintenance of semantic representations in working memory involves a distinct capacity (e.g., Majerus et al, 2004 ; Shivde and Anderson, 2011 ; Nishiyama, 2014 ).…”
mentioning
confidence: 99%